"Culture and Conceptualisation of Scientific Terms: An Analysis of the Concepts "Weight" and "Mass" in Arabic and French (KEMANUSIAAN The Asian Journal of Humanities, 2016)
Studies on difficulties in understanding scientific terms have shown that the problem is more serious among non-Western learners. The main reasons for this are the learners' pre-existing knowledge of scientific terms, their native language incommensurability with Western languages, and the polysemy of the words used to denote scientific concepts. The current study is an analysis of the conceptualisation of scientific concepts in two culturally different languages, i.e. Arabic and French, which represent a non-Western language and a Western language respectively. Physics concepts which are considered as some of the most challenging concepts for non-Western languages (Loo 2005; Aranador 2005) were selected for analysis. To this end, the terms that refer to two physics concepts, "weight" and "mass" in Arabic ????? (wazn) and ??????? (kutla) and in French poids and masse were semantically analysed. The analysis of the concepts in both languages is informed by the prototype theory by Rosch (1973; 1975), idealised cognitive models (ICMs) by Lakoff (1987), and conceptual metaphor and conceptual metonymy by Lakoff and Johnson (2003). The data for analysis were retrieved from two comparable Arabic and French corpora, namely the ArabiCorpus and the Concordancier-Corpus Français. The results suggest that there are both similarities and differences between the Arabic and French concepts in terms of meanings, prototypes, and metaphorical as well as metonymic semantic extensions. These findings support the argument that the human conceptual system is related to our environmental and cultural experiences and also importantly, validate previous claims on the need for educators to be cognizant of the culturally relevant meanings of scientific words found in everyday language that may impede learners' understanding of scientific concepts.